Knowledge, attitude and practice on hygiene of Kampung Sungai Karang Darat residents and its related factors November 2003 - Mohamed @ Salleh, Ahmad Zakiyy; Pa'adek, Azimi; Hamzah, Alya Ilma Fadhilah; Zulkeply, Aznida; Mohd. Rosli, Najwa Hanim; Johari, Bushra; Mohd. Sahid, Ermi Nieza; Haron, Hasdy; Mohd. Razali, Hasmein; Jaafar, Jasri; Taib, Mai Nurul Ashikin; Mohd. Mokhtar, Mohd. Amin; et al. (International Islamic University Malaysia, 2003)
Introduction: A cross-sectional study was conducted in September 2003 to evaluate the Knowledge, Attitude and Practice (KAP) level on hygiene of Kampung Sungai Karang Darat residents and its related factors.